The Influence of Financial Literacy, Financial Inclusion, and Lifestyle on Students’ Consumptive Behavior: The Mediating Role of Lifestyle - Muhammad Agusalim; Wahda; Lalu Masyhudi (Journal of Economics and Management, 2026)
This study examines the effect of financial literacy and financial inclusion on students’ consumptive behavior, with lifestyle as a mediating variable. A quantitative approach was employed using survey data collected from students receiving BIDIKMISI and KIP-K scholarships at Universitas Terbuka Malang. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that financial literacy has a significant negative effect on consumptive behavior, indicating that higher financial knowledge reduces excessive consumption. In contrast, financial inclusion does not have a significant effect. Lifestyle has a significant positive effect on consumptive behavior and partially mediates the relationship between financial literacy and consumptive behavior. However, lifestyle does not mediate the relationship between financial inclusion and consumptive behavior. These findings highlight the importance of strengthening financial literacy and promoting a balanced lifestyle to reduce consumptive behavior among students.